Linguistic study of the Chenchus of Andhra Pradesh - Trivedi, G. M. (Govind Mohan), 1942- (Anthropological Survey of India, Govt. of India, 1978)
On the phonology and morphology of Chenchu, a Telugu dialect; includes folk literature of the Chenchus.